2013
DOI: 10.1002/jlcr.3018
|View full text |Cite
|
Sign up to set email alerts
|

Tropane‐derived 11C‐labelled and 18F‐labelled DAT ligands

Abstract: Radiolabelling of cocaine-derived 3-phenyltropanes for dopamine transporter positron emission tomography with (18) F and (11) C is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…However, because of constraints imposed by radionuclides other than 18 F in combination with the kinetic profiles of the available radiotracers in the required imaging protocols, there remains a need for a tracer with optimal properties for quantitative imaging of multiple animals from a single radiosynthesis. Although, a plethora of agents have been developed for imaging of DAT, [1][2][3] all may suffer in varying degrees from lack of selectivity, unfavorable kinetics, and adverse metabolism. A particular issue is the pharmacological selectivity of tracers for DAT versus serotonin transporters (SERT), and to a lesser extent (because of their low abundance) noradrenaline transporters (NET).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of constraints imposed by radionuclides other than 18 F in combination with the kinetic profiles of the available radiotracers in the required imaging protocols, there remains a need for a tracer with optimal properties for quantitative imaging of multiple animals from a single radiosynthesis. Although, a plethora of agents have been developed for imaging of DAT, [1][2][3] all may suffer in varying degrees from lack of selectivity, unfavorable kinetics, and adverse metabolism. A particular issue is the pharmacological selectivity of tracers for DAT versus serotonin transporters (SERT), and to a lesser extent (because of their low abundance) noradrenaline transporters (NET).…”
Section: Introductionmentioning
confidence: 99%
“…Human PET studies of [ 11 C]CFT demonstrated high accumulations in regions of dopaminergic innervation, and good pharmacokinetics suitable for modeling to obtain estimates of transporter numbers in normal and disease conditions. Over the decades since introduction of [ 11 C]CFT in the early 1990s, a very large number of analogs have been synthesized which incorporate 11 C or 18 F [ 59 ]. Several of the fluorine-18 labeled 3-phenyltropanes (e.g., [ 18 F]FE-PE2I; Figure 2 ) [ 60 , 61 ] have been translated into human studies, and together with continued use of [ 11 C]CFT, provide DAT radioligands for numerous clinical research studies.…”
Section: Neuronal Membrane Dopamine Transporters (Dat)mentioning
confidence: 99%
“…Dopamine transporter (DAT) imaging agents are highly sought after for studies of the availability of this presynaptic binding site in preclinical research and clinical application …”
Section: Introductionmentioning
confidence: 99%
“…Although direct labelling superficially appears to be the more elegant route, it suffers from low radiochemical yields, and most approaches to overcome this issue do not translate well into the available automated synthesis modules, for example, due to the use of microwave reactors . This is a major issue for clinical application, because routine production of sufficient doses requires starting radioactivities well above the amounts considered to be safe for manual handling …”
Section: Introductionmentioning
confidence: 99%